A situação do alemão em Tunápolis e Cunha Porã, Santa Catarina: dimensão diarreligiosa - Wehrmann, Clarí (2016)
This study aims to investigate the degree of maintenance of the German variety in plurilingual contexts – German variety and Portuguese variety- , in Tunápolis (SC) and Cunha Porã (SC) cities. The presence of the German language in these places depends on the german settlement, however, there is a differential between these places – Tunápolis was settled by catholics and Cunha Porã, predominantly, by Lutheran germans. Tunápolis is a small community with 4.633 inhabitants, secluded; and the german and catholic ethnic predominate. While Cunha Porã is bigger, with 10.613 inhabitants, and shows more mobility; its ethnic is heterogeneous and 95% of the population is divided into 50% catholics and 50% lutherans. In face of these results, Tunápolis is considered a place for a catholic research and Cunha Porã, a place for a lutheran one. Both places are plurilingual contexts where it is observed a permanent linguistic contact between the German varieties and the Portuguese varieties. In these contexts, it is intended to ascertain the degree of maintenance of the sanguine and spiritual kinship terms in German variety as a native language and belong to the catholic and lutheran confessions.The research methodology follows the theoretical principles of Thun Relational Multidimensional Dialectology (1996, 1998, 2005a, 2005b, 2009, 2010, 2012). From this perspective, in order to observe which the real condition of the German variety in different social backgrounds, the research aims in diastratic, diageracional, diagenerical and diarreligious dimensions. Based on these dimensions, eight informants are selected in every point of the research; a general and lexical questionnaire, text readings and free conversation with the theme based on sanguine and spiritual kinship terms are applied to them. These data from the interviews are the corpus analysed. The sanguine kinship choice is due to the importance and the presence of the family in the German culture. In the bibliographic review, it is observed an intrinsic relation among german immigration, church and German variety. For catholics, the German language is a communication tool, since the basis of this confession is the Latin. For the Lutherans, otherwise, besides being a means of communication, German is also a religious symbol for with the first translation of the Bible to the German language made by Martin Luther and, through the preaching and so literating everyone by him, the Lutheran Confession came about. The results of other researches of the german variety maintenance line, carried out in Brazil, show a tendency of a higher degree of the german variety maintenance by the lutherans, but there are no corroborative empirical data. This present research is under the same assumption and, based on the results determined, I indicated, with empirical data, that are the lutherans who more apply the sanguine terms in German. Indirectly, it is also observed a great interference from the church as a domain and indentity group, in favor of keeping a minority language. Because of its nature, the work includes in the line of research diversity and language change, more precisely in the area of german varieties maintenance in plurilingual contexts.